Preparation and characterization of boron containing thiol-ene photocured hybrid coatings - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE SA, 2012)
In this study, flame retardant, 4-vinylphenyl boronic acid containing coatings were prepared by thiol-ene polymerization. The photopolymerization kinetics of thiol-ene based formulations was investigated by real time infrared spectroscopy. The experiments showed that as the amount of boronic acid was increased, flame retardant properties of the coatings were also increased. Tensile test results showed that boronic acid groups strengthened the polymeric network. DSC results revealed that the addition of thiol causes Tg values of the coatings to decrease. On the other hand acid groups improved the hydrophilicity of the coatings. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Thiol-ene polymerization; UV curing; Flame retardant; 4-Vinylphenyl boronic acid; PHOTOINDUCED POLYMERIZATION; CROSS-LINKING; PHOTOPOLYMERIZATION; ACRYLATE; NETWORKS; SYSTEMS; ACID